Differentiation and Inheritance of the Number of Dermal Ridges on the Thenar and Hypothenar of the Palm - Buchwald, Wiesław (Anthropological Review, 1994)
Differentiation and Inheritance of the Number of Dermal Ridges on the Thenar and Hypothenar of the Palm were determined for 260 sets of parents and 290 children. The data obtained were statistically analysed.-The traits analysed did not show any bilateral or intersexual differences. The correlations between parents and children indicate genetic determination of the number of dermatoglyphs in both studied areas of the palm.